2010
DOI: 10.1007/s10067-009-1341-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of systemic sclerosis in Split–Dalmatia county in Southern Croatia

Abstract: This study aims to evaluate the prevalence of patients with systemic sclerosis (SSc) in Split-Dalmatia County in Southern Croatia. Patients were recruited from the medical records of University Hospital Split. Our Department of Rheumatology and Clinical Immunology is the only tertiary referral center for the Split-Dalmatia County, which has a population of 313,365 inhabitants aged over 18 years. Diagnoses were verified by medical record review. Cases of localized scleroderma (morphea and linear disease) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
1
17
0
1
Order By: Relevance
“…Our study estimated incidence and prevalence in the UK to be higher than previously reported in Norway, Croatia, Greece, France, Taiwan, and Australia [6, 7, 10, 12, 13, 16], similar to the USA, Sweden, and Spain [11, 14, 15], and lower than in Italy and Canada [3, 4]. Our findings were consistent with other large population-based studies in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study estimated incidence and prevalence in the UK to be higher than previously reported in Norway, Croatia, Greece, France, Taiwan, and Australia [6, 7, 10, 12, 13, 16], similar to the USA, Sweden, and Spain [11, 14, 15], and lower than in Italy and Canada [3, 4]. Our findings were consistent with other large population-based studies in Caucasians.…”
Section: Discussionsupporting
confidence: 90%
“…Studies published since this have continued to report high incidences in Southern Europe (Spain, Croatia and Italy) [3, 11, 12] but contradictory rates in Northern Europe with low annual incidence of 6–11 per million in Norway [13] and a higher rate 19/million person-years in Southern Sweden [14]. Incidence and prevalence in the USA, Canada, and Australia are reported at the higher end of this range [4, 15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated point prevalence was 27.7 cases per 100 000 persons, and the estimated mean annual incidence was 2.3 cases per 100 000 persons per year . Radic et al conducted a retrospective analysis of medical records from Split University Hospital in Split‐Dalmatia County, Croatia, to estimate the prevalence of SSc during 2008 . The 1‐year prevalence was 15.6 cases per 100 000 persons in southern Croatia using the 1980 ACR criteria only .…”
Section: Resultsmentioning
confidence: 99%
“…Radic et al conducted a retrospective analysis of medical records from Split University Hospital in Split‐Dalmatia County, Croatia, to estimate the prevalence of SSc during 2008 . The 1‐year prevalence was 15.6 cases per 100 000 persons in southern Croatia using the 1980 ACR criteria only . Bajraktari et al conducted a retrospective analysis of medical records in the municipalities of Dukagjini Plain, Kosovo, to estimate the 2010 point prevalence and the mean annual incidence of SSc during a 6‐year period, from 2005 to 2010 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation